Dashboards as Conduits for Collaborative Planning - DeLoyde, Carolyn; Donald, Betsy (Canadian Planning and Policy / Aménagement et politique au Canada, 2024)
Dashboards are not new to planning and much has been written about them especially around the user experience and technological failures. Missing in the literature, however, is a discussion around the processes behind making an urban data dashboard and what that process can do in terms of building relationships and supporting collaborative planning. Through a case study of a dashboard making process in Kingston, Ontario between September 2020 and August 2023, the authors show how the dashboard making process led to technological innovation, improved collaboration amongst the partners, strengthened relationships and improved organizational and management processes for all partners involved. More than a technocratic or rational planning exercise, dashboard making has the potential to be a conduit for collaborative planning which is a cornerstone of a healthy, democratic society.